2016
DOI: 10.1097/iae.0000000000000938
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Idiopathic Foveomacular Retinoschisis

Abstract: Idiopathic foveomacular retinoschisis is not inherited or associated with myopia, vitreomacular traction syndrome, optic pit, or glaucoma but is associated with older age, unilaterality, hyperopia with short axial length, complete posterior vitreous detachment, and weak leakage from the optic disk on fluorescein angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Overall, these findings are likely inconclusive due to the low number of patients studied. 3,22 Also, FA of SNIFR reveals no active leakage or other abnormalities, consistent with the initial presentation of the patient in this case report. 3 The clinical presentation on both fundoscopy and OCT imaging combined with the lack of any other attributable etiology suggests that the patient's unilateral foveoschisis is likely idiopathic in nature.…”
Section: Idiopathic Foveoschisis and Rarer Causessupporting
confidence: 86%
“…Overall, these findings are likely inconclusive due to the low number of patients studied. 3,22 Also, FA of SNIFR reveals no active leakage or other abnormalities, consistent with the initial presentation of the patient in this case report. 3 The clinical presentation on both fundoscopy and OCT imaging combined with the lack of any other attributable etiology suggests that the patient's unilateral foveoschisis is likely idiopathic in nature.…”
Section: Idiopathic Foveoschisis and Rarer Causessupporting
confidence: 86%
“…Therefore, this case may be called occult optic disc coloboma-associated maculopathy. Cases with retinal schisis extending from the disc to the macula despite having funduscopically normal optic disc have been recently reported [ 27 ]. These cases had a predisposition to occur in emmetropic eyes of older patients and in the presence of preoperative PVD.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of vitreous traction in the pathogenesis of macular retinoschisis remains controversial [ 16 ]. Some studies have reported that vitrectomy is effective for macular retinoschisis in which no obvious pit was detected [ 17 ] or for idiopathic macular retinoschisis [ 18 ]. Thus, the mechanism by which vitrectomy resolves macular lesions is not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%